Evaluation of the Position Error of Wearing Surgical Masks During Radiotherapy in Head and Neck Cancer Patients - Chan SH; Huang YY; Tsai SH; Wang JC; Chen YR; Kang CL (Cancer Management and Research, 2022)
Shan-Ho Chan,1 Ya-Yu Huang,2 Shu-Huei Tsai,2 Jui-Chu Wang,3 Yi-Ren Chen,2 Chen-Lin Kang1,2 1Department of Medical Imaging and Radiology, Shu-Zen Junior College of Medicine and Management, Kaohsiung, Taiwan; 2Department of Radiation Oncology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 3Department of Anatomical Pathology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, TaiwanCorrespondence: Chen-Lin Kang, Department of Radiation Oncology, Kaohsiung Chang Gung Memorial Hospital, No. 123, Dapi Road, Niaosong Dist, Kaohsiung, 833, Taiwan, Tel +886 7 7317123#7115, Fax +886 7 7322813, Email k1074.kang@gmail.comPurpose: Wearing a mask during the coronavirus disease 2019 epidemic (COVID-19) is a preventive way to reduce droplet and aerosol transmission. The purpose of this study was to evaluate the position error of wearing a surgical mask during radiotherapy in head and neck cancer patients.Patients and Methods: We collected and analyzed 2351 kV X-ray image records of 81 patients with head and neck cancer who underwent image-guided radiotherapy (IGRT). Patients with/without a surgical mask were divided into the head-neck (HN) mask group and head-neck-shoulder (HNS) mask group. The position error in the X (left-right), Y (superior-inferior), Z (anterior-posterior), 3D (three dimensional) vectors, as well as the pitch and yaw axes were compared between the four groups.Results: We found that patients wearing surgical masks in the HN mask group showed no significant differences in the mean position error of the different types of headrest (p> 0.05). In the HNS mask group, only the type C headrest group showed significant differences (P < 0.05). The X axis values were − 0.05± 0.07 and − 0.11± 0.01 cm (P = 0.04), and the pitch axis values were 0.34± 0.29° and 0.83± 0.08° (P = 0.01).Conclusion: The mean position error of most patients wearing surgical masks was not greater than patients without a surgical mask. Patients wearing while receiving treatment is a low-cost and easy-to-implement prevention method.Keywords: COVID-19, head and neck cancer, image-guided radiotherapy, setup error